Inflammatory bowel disease and oral health: systematic review and a meta-analysis - Papageorgiou, Spyridon N.; Hagner, Martin; Nogueira, Andressa Vilas Boas [UNESP]; Franke, Andre; Jäger, Andreas; Deschner, James (Wiley, 2017)
Background: The objective of this systematic review was to systematically investigate whether there is an association between inflammatory bowel disease (IBD) and oral health. Methods: Literature searches for randomized and non-randomized studies were performed up to January 2017. Risk of bias within studies was assessed with the Downs and Black checklist. Across-studies risk of bias was assessed with the GRADE framework. Quantitative synthesis was conducted with random-effects meta-analyses. Results: A total of 9 cross-sectional studies including 1297 patients were included. IBD was associated with increased risk of periodontitis (332 more patients per 1000 patients; 95% confidence interval (CI): 257–388 patients; p < 0.001) compared to non-IBD patients. Additionally, the Decayed-Missing-Filled-Teeth index of IBD patients was significantly worse than non-IBD patients (mean difference: 3.85; 95% CI: 2.36–5.34; p = 0.005). Patients with ulcerative colitis had considerably worse oral health for most of the assessed factors, while the quality of overall evidence ranged from high to low, due to the observational nature of contributing studies. Conclusions: Inflammatory bowel disease was associated with significantly higher risk of periodontitis and worse oral health compared to non-IBD patients. However, longitudinal studies are needed in order to establish a causality link between IBD and periodontal disease.
Keywords: Crohn's disease; inflammatory bowel disease; meta-analysis; oral health; periodontal disease; systematic review; ulcerative colitis